"Distant Toleration": The Politics of Solidarity Work among Turkish and Syrian Women in Southern Turkey. (14th July 2021) - Dağtaş, Seçil; Can, Şule
Abstract: This article examines the politics of solidarity with and among refugee women in Turkey's southern borderlands. Drawing on ethnographic research in Hatay, we focus on Syrian- and Turkish-led women's organizations, whose solidarity work contextually entangles organized acts of care and support with social hierarchies, tensions, and mutual distance. These gendered social spaces complicate the scholarly critiques of depoliticization in refugee assistance by governmental and civil society organizations, and the charity–solidarity distinction on which such critiques often rely. They require a rethinking of solidarity with refugee women beyond the terms of right-based political activism.